2012
DOI: 10.1016/j.vetpar.2012.03.043
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of simple random sampling to observed variations in faecal egg counts

Abstract: It has been over 100 years since the classical paper published by Gosset in 1907, under the pseudonym "Student", demonstrated that yeast cells suspended in a fluid and measured by a haemocytometer conformed to a Poisson process. Similarly parasite eggs in a faecal suspension also conform to a Poisson process. Despite this there are common misconceptions how to analyse or interpret observations from the McMaster or similar quantitative parasitic diagnostic techniques, widely used for evaluating parasite eggs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…Only counting eggs in the gridded area appears to account for this aggregation at higher levels of egg densities; the number of eggs present at lower densities, however, was still underestimated. Therefore, although counting of the entire chamber rather than solely the gridded area is considered to improve precision due to the reduced dilution factor (Torgerson et al, 2012), the greater degree of measurement error seen in the present study clearly outweigh this benefit and supports the approach recommended by FECPAK to count the number of eggs under one or both gridded areas rather than the full chamber (Coles, 2003).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Only counting eggs in the gridded area appears to account for this aggregation at higher levels of egg densities; the number of eggs present at lower densities, however, was still underestimated. Therefore, although counting of the entire chamber rather than solely the gridded area is considered to improve precision due to the reduced dilution factor (Torgerson et al, 2012), the greater degree of measurement error seen in the present study clearly outweigh this benefit and supports the approach recommended by FECPAK to count the number of eggs under one or both gridded areas rather than the full chamber (Coles, 2003).…”
Section: Discussionsupporting
confidence: 60%
“…This may reflect the fact that the minimum detection limit is 5 epg with the Mini-FLOTAC compared to 30 epg with FECPAK grids. Torgerson et al (2012) previously identified that applying a larger multiplication factor to raw FECs, as is necessary with the FECPAK, leads to a greater inflation of variation (reduced precision) in the final FEC. Underestimated FECs observed at the lower egg densities of 10 and 50 epg are expected with the FECPAK grid counts as the minimum detection limit is 30 epg.…”
Section: Discussionmentioning
confidence: 99%
“…before or after treatment. In a previous studies in the northeast of Spain, Cooperia oncophora was not the most prevalent GIN in cattle, representing the 9.6-19.7% of species (Almería et al, 1996); on the other hand, the present study in herds was carried out mainly between autumn and winter, when mean In horses, there is a lack of consensus on study design, data analysis and data to evaluate AR based on a FEC reduction test (Torgerson et al, 2012;Vidyashankar et al, 2012). In the present study, susceptibility was defined as a reduction of FEC higher than 90% for BZ and PYR, and 95% for MLs.…”
Section: Discussionmentioning
confidence: 68%
“…It would be wrong to conclude there are no parasite eggs in the faeces as even quite substantial positive real counts can result in zero eggs being observed on the McMaster slide due to Poisson errors. For a fuller explanation see Torgerson et al (2012)). For example, with a dilution factor of 50, even if the true egg count is 100 epg, there is still a probability of 13.5% of observing zero eggs.…”
Section: Discussionmentioning
confidence: 99%
“…The random distribution of eggs within a faecal sample will conform to a Poisson process and thus repeat calculations of eggs per gram from the same faecal sample will be subject to Poisson errors (Torgerson et al, 2012). Therefore there is inevitable variability in evaluating faecal egg counts even with a highly precise laboratory technique due to this random variation.…”
Section: Introductionmentioning
confidence: 99%